2016
DOI: 10.1021/acsmacrolett.6b00184
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive, Optically Active Poly(diphenylacetylene) Having a Bulky Chiral Side Group

Abstract: A highly emissive, optically active poly-(diphenylacetylene) derivative, NpSi*-PDPA, was synthesized by introducing a bulky chiral pendant group into the polymer chain. NpSi*-PDPA exists in a glassy state having a highly disordered and amorphous structure. Hence, the fractional free volume is quite high, i.e., 0.29. NpSi*-PDPA emits a green light in solution and a yellow light in film. This polymer is quite emissive, as the photoluminescence (PL) quantum yield is 56.1% in solution and 6.2% in film, and the PL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…These results indicated that a predominantly one-handed helical conformation was induced in the polymer backbone by thermal annealing owing to the effect of the optically active pendants (h-poly-2S). A similar thermal annealing was necessary for poly-4S to form the preferred-handed helical conformation (h-poly-4S) [27,36]. This result was attributed to steric hindrance between the neighboring pendant phenyl rings, which was large enough to prevent poly-2S and poly-4S from being transformed into their preferred-handed helical conformations after the introduction of the optically active pendants.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…These results indicated that a predominantly one-handed helical conformation was induced in the polymer backbone by thermal annealing owing to the effect of the optically active pendants (h-poly-2S). A similar thermal annealing was necessary for poly-4S to form the preferred-handed helical conformation (h-poly-4S) [27,36]. This result was attributed to steric hindrance between the neighboring pendant phenyl rings, which was large enough to prevent poly-2S and poly-4S from being transformed into their preferred-handed helical conformations after the introduction of the optically active pendants.…”
Section: Resultsmentioning
confidence: 97%
“…These results indicated that a predominantly one-handed helical conformation was induced in the polymer backbone by thermal annealing owing to the effect of the optically active pendants (h-poly-2S). A similar thermal annealing was necessary for poly-4S to form the preferred-handed helical The circular dichroism (CD) spectrum of poly-2S showed almost no circular dichroism (CD) in the wavelength region longer than 300 nm ascribed to the absorption of the polymer backbone in N,N-dimethylformamide (DMF) immediately after the preparation of the sample (Figure 2a) [27,[32][33][34][35]. However, an apparent Cotton effect was observed around 400 nm after one day.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…21 Very recently, a similar thermal annealing effect on the CD intensity was reported for an optically active poly(diphenylacetylene) bearing a bulky pendant. 13 The chiral recognition abilities of poly-3 and h-poly-3 as CSPs for HPLC were evaluated by coating them on macroporous silica gel. The DMF solutions of poly-3 and h-poly-3 were coated on macroporous silica gel to give coated-type packing materials, 22 which were then packed into a stainless steel column (25 © 0.20 cm (i.d.))…”
mentioning
confidence: 99%